Getting to Know Teacher Administration in Teaching and Learning Activities for Islamic Religious Education - Septianingrum, Amelia Dwi; Ichwanudin (Tahta Media Group, 2025)
This study aims to analyse the implementation of teacher administration and teaching and learning activities at SMP Negeri 5 Ponorogo, with a focus on the role of teachers in creating an effective learning environment. The qualitative research method uses an observational, interview, and documentation approach. The research subjects comprised Islamic Education (PAI) teachers in grade 8 with teaching experience at the school. Data analysis techniques involved processing information obtained from interviews and documents, which were then reviewed and developed according to the author's perspective. The research results indicate that mastery of teacher administration significantly influences the effectiveness of planning and implementing the learning agenda. Teachers who understand their duties and responsibilities better can plan lessons more effectively, thereby facilitating students' comprehension of the material. In conclusion, developing teachers' managerial skills is crucial for creating a conducive and effective learning environment, which ultimately positively impacts students' learning outcomes.